1997
DOI: 10.1136/adc.76.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hypoxaemia in hospital admissions with acute lower respiratory tract infection in a developing country

Abstract: Since oxygen has to be given to most children in developing countries on the basis of clinical signs without performing blood gas analyses, possible clinical predictors of hypoxaemia were studied. Sixty nine children between the ages of 2 months and 5 years admitted to hospital with acute lower respiratory tract infection and an oxygen saturation (SaO 2 ) < 90% were compared with 67 children matched for age and diagnosis from the same referral hospital with an SaO 2 of 90% or above (control group 1), and 44 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 11 publications
2
64
0
6
Order By: Relevance
“…Lobar consolidation is usually associated with bacterial pneumonia which is often associated with fatal outcome especially in children under five in developing countries like Bangladesh [13], mostly due to overwhelming hypoxemia resulting from ventilation perfusion mismatch from para-pneumonic shunting. [14,16,17]. Sepsis may be the consequences of lobar pneumonia, as observed in our cases, frequently associated with high case-fatality rate [14].…”
Section: Discussionsupporting
confidence: 60%
“…Lobar consolidation is usually associated with bacterial pneumonia which is often associated with fatal outcome especially in children under five in developing countries like Bangladesh [13], mostly due to overwhelming hypoxemia resulting from ventilation perfusion mismatch from para-pneumonic shunting. [14,16,17]. Sepsis may be the consequences of lobar pneumonia, as observed in our cases, frequently associated with high case-fatality rate [14].…”
Section: Discussionsupporting
confidence: 60%
“…12 Findings of the study revealed that grunting (p=0.009), nasal fl aring (p=0.008), subcostal (p=0.001) and intercostal (p=0.000) retractions were highly but suprasternal retraction was signifi cantly (p=0.024) associated with hypoxemia which is in agreement with various other studies have reported that grunting and nasal fl aring were signifi cantly associated with hypoxemia. 1,18,23 During a study, Rao et al (2012) 16 found that chest wall retraction was found to be the most sensitive indicator, and cyanosis was the most specifi c indicator for hypoxemia. Kuti has also confi rmed the relevance of the study as he recently reported that children that grunt and are centrally cyanosed should preferentially commenced on oxygen therapy even when there is no facility to confi rm hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Spirometry may also alert physicians to the possibility of mild pulmonary disorders, and it may be used for monitoring patients with conditions such as asthma and cystic fibrosis. Similarly, pulse oxymetry may detect reduced blood oxygenation at earlier stages than central cyanosis 68 . Therefore, we join the calls to incorporate pulse oximetry and spirometry into the PE, and add hand-held oximeters and spirometers to the stethoscope, sphygmomanometer and reflex hammer that a doctor already uses during patient examination 69 .…”
Section: Discussionmentioning
confidence: 99%